Chemical characterization and ruminal degradation of waste from fruit fly production - PINTO RUIZ, RENE; Ramirez Diaz, Roselia; Pérez Pérez, Tomas Alberto; Pérez Escobar, María Guadalupe; Arredondo Gordillo, José (Acta Universitaria, 2026)
It was characterized the chemical composition and ruminal fermentation of three waste products generated after harvesting fruit fly larvae from two production industries of Anastrepha ludens and Ceratitis capitata. T1 corresponded to the A. ludens diet, while T2 (Cellulose) and T3 (Grinded) came from C. capitata diets. The results were evaluated using the GLM procedure. Crude protein was higher in T1 and T2 than in T3 (8.89%) (p < 0.05). Dry matter degradation was similar between T1 and T2 (45.61% and 45.98%) and higher than in T3 (p < 0.05). In terms of kinetics, the maximum gas volume was highest in T1 (331.73 ml g⁻¹ DM). These materials provide the minimum protein required to meet the requirements of rumen microbes and their inclusion in ruminant diets could stimulate the use of waste, promoting the circular economy.